The impact of neoadjuvant therapy on the histopathological features of pancreatic ductal adenocarcinoma – A systematic review and meta-analysis. (April 2017) - Schorn, Stephan; Demir, Ihsan Ekin; Reyes, Carmen Mota; Saricaoglu, Cemil; Samm, Nicole; Schirren, Rebekka; Tieftrunk, Elke; Hartmann, Daniel; Friess, Helmut; Ceyhan, Güralp Onur
Highlights: Neoadjuvant therapy in pancreatic ductal adenocarcinoma is associated with a more favorable tumor stage. Neoadjuvant therapy in pancreatic ductal adenocarcinoma is associated with a less incidence of tumor-positive lymph nodes. Neoadjuvant therapy in pancreatic ductal adenocarcinoma is associated with a less incidence of tumor-positive resection margins. Neoadjuvant therapy in pancreatic ductal adenocarcinoma is associated with a less incidence of neural invasion. Neoadjuvant therapy in pancreatic ductal adenocarcinoma is associated with a less incidence of G3-tumros. Abstract: Background: Due to increased rates of curative tumor resections exceeding 60% after FOLFIRINOX-treatment, neoadjuvant therapy/NTx is increasingly recognized as an effective therapy option for downstaging borderline or locally advanced pancreatic ductal adenocarcinoma/PDAC. Yet, the effects of NTx on the common histopathological features of PDAC have not been systematically analysed. Therefore, the aim of the current study was to assess the impact of NTx on relevant histopathological features of PDAC. Patients and methods: Biomedical databases were systematically screened for predefined searching terms related to NTx and PDAC. The Preferred-Reporting-Items-for-Systematic-review-and-Meta-Analysis/PRISMA-guidelines were used to perform a systematic review and meta-analysis. Articles meeting the predefined criteria were analysed on relevance, and a meta-analysis was performed. Results: A total of 9031 studies could be identified that analysed the effect of NTx on PDAC. Only 35 studies presented comparative data on the histological features of neoadjuvantly treated vs. upfront resected PDAC patients. In meta-analyses, the beneficial effect of NTx was reflected by reduced tumor size (T1/2: RR 2.87, 95%-CI: 1.52–5.42, P  = 0.001, T3/4: RR 0.78, 95%-CI: 0.69–0.89, P  = 0.0002), lower N-Stage (N0: RR 2.14, 95%-CI: 1.85–2.46, P  < 0.00001, N1: RR 0.59, 95%-CI: 0.53–0.65, P  < 0.00001), higher R0-rates (R0: RR 1.13, 95%-CI: 1.08–1.18, P  < 0.00001, R1: RR 0.66, 95%-CI: 0.58–0.76, P  < 0.00001), less perineural invasion (Pn1: RR 0.78, 95%-CI: 0.73–0.83, P  < 0.00001), less lymphatic vessel invasion (RR: 0.50, 95%-CI: 0.36–0.70, P  < 0.0001) and fewer G3-tumors (RR 0.82, 95%-CI: 0.71–0.94, P  = 0.005). Conclusions: NTx in PDAC seems to exert its beneficial effect in borderline or locally advanced PDAC over genuine tumor downstaging. Thus, although at least 40% of all NTx treated patients remain unresectable even with modern NTx regimes, neoadjuvantly treated PDAC showed not only increasing resectability rates especially after FOLFIRINOX, but even reach a lower tumor stage than primarily resected PDAC.